Influence of ultra-processed foods on prevalence of inadequacy in Portuguese adults and elderly. (30th September 2020) - Costa de Miranda, R; Rauber, F; Moraes, M; Rodrigues, S; Bertazzi Levy, R
Abstract: Background: Ultra-processed foods (UPF) consumption has been widely associated with low diet quality. We aim to investigate its energy contribution and influence on prevalence of nutrient inadequacy in Portugal. Methods: Cross-sectional representative study involving 3102 adults and 750 elderly enrolled in the 2015-2016 National Food, Nutrition and Physical Activity Survey. Dietary intake was assessed by two non-consecutive 24h recalls. Food items were classified according to the NOVA system. Total energy intake and energy contribution provided by UPF group were determined. Inadequate intake was evaluated across quintiles (Q) of UPF consumption by adjusted Poisson regressions. We adjusted the usual intake estimate by Multiple Source Method and considered the World Health Organization (WHO) recommendations. Results: UPF contributed with 24% and 16% of daily energy intake in adults (1904 kcal/day) and elderly (1603 kcal/day), respectively. In both age groups, practically all individuals had inadequate intake of sodium, while about a half or more of population had inadequate intake of fibre and potassium. As the dietary share of UPF increased, the prevalence of inadequacy of free sugars (PR = 1.53 for adults and 1.56 for elderly) and saturated fat (PR = 1.18 and 1.15, respectively) increased significantly. In adults, this same trend was also seen for fibre (PR = 1.03) and potassium (PR = 1.12). Particularly relevant was the increase in prevalence of inadequacy of free sugar from 10.5% (Q1) to 67.6% (Q5) in adults and 5.8% (Q1) to 41.8% (Q5) in elderly. Prevalence of inadequacy of saturated fat raised from 27.3% (Q1) to 68.9% (Q5) in adults and 29.4% (Q1) to 46.8% (Q5) in elderly. Conclusions: Effective strategies are needed to reduce UPF consumption among Portuguese adults and elderly in order to prevent them from diet-related non-communicable diseases. Funding: FAPESP 2018/07391-9, 2019/05972-7 (MCR), 2016/14302-7 (FR); POCI-01-0145-FEDER-032090. Key messages: Ultra-processed food contributes with 24% and 16% of daily energy intake in Portuguese adults and elderly. As the ultra-processed food consumption increases, the prevalence of inadequacy of free sugars and saturated fat increases for both, while inadequacy of fiber and potassium also increases for adults.